Macrozoobentos Diversity In The Mangrove Ecosystem In Bagan Asahan Village, North Sumatra Province - Saragih, Maryanto; Sinaga, Mardame Pangihutan; Saragih, Ewin Handoco (Jurnal Ilmiah Platax, 2024)
Macrozoobenthos are organisms that live by crawling, sticking, burrowing, and burrowing both at the bottom of the water and on the surface of the water bottom. Macrozoobenthos that live in mangrove areas mostly live on hard sediments to mud. The existence of macrozoobenthos can be influenced by various environmental factors such as the physical, chemical, and biological properties of water. This research aims to determine diversity, uniformity, and the macrozoobenthos dominance of the mangrove ecosystem in Bagan Asahan Village. The method used in this research is to combine two methods, namely the square method and the line transect method. The quadratic method is used to see the macrozoobenthos found in the quadratic method in a biological system, while the line transect method is used as a point to determine the description of the macrozoobenthos. The results of the research show that there are 8 species of macrozoobenthos consisting of 3 classes with a total of 179 individuals. The diversity of macrozoobenthos in the mangrove ecosystem area in Bagan Asahan Village is classified as moderate with a diversity index H'' ranging from 1.54-2.01, the uniformity index is classified as stable ranging between E= 0.76-0.99 and the dominance index is low, ranging between C= 0.14-0.31. Keywords: Tanjung Balai, Macrozoobenthos, Mangrove, Diversity